Propagation models for microcellular communication systems - Gan, Sam Sam (2008)
Working principles of the ray-tracing model proposed in [Ang99] is studied extensively. A ray-tracing simulation program predicting propagation loss has been written in C++ based on multiple image method. The program is used to verify technique proposed in [Ang99], which can include diffraction from multiple parallel and coplanar/non-coplanar orthogonal edges.